Optional course on spinocerebellar ataxia type 2 at the Universidad de Ciencias Médicas de Holguín - Ana Luisa Berrillo-Caisés; Julio César Rodríguez-Díaz; Dania de las Mercedes Zayas-Aldaya; Yasmany González-Garcés; Reidenis Torres-Vega (Revista Información Científica, 2022)
Introduction: it recently began the training of professionals in a new modality of Programas Técnico Superior de Ciclo Corto (Short Cycle Superior Technical Programs) in the Clinical Neurophysiology specialty, at the Universidad de Ciencias Médicas de Holguín, attending to the high incidence of neurological diseases, such as spinocerebellar ataxia type 2, which constitutes a serious health problem in Cuba. This is an elective course program that addresses this topic and contributes to the knowledge of this disease, in order to improve research and possible treatments.